THE NEED TO INCREASE SAFETY AT UNCONTROLLED AERODROMES (Perner's Contacts, 2012)
This article analyzes the problem of heavy traffic on small uncontrolled aerodromes, which is not solved and due to this arise emergency situations, and suitability of introducing surveillance monitoring system for AFIS officers to increase safety of general aviation. In this article it is also mentioned appropriate procedure for determining on which aerodromes should be obligatory surveillance system.
Keywords: AFIS, AFIS Officer, ATZ, ADS-B, MLAT